Acanthoceratidae y zonación de ammonites del Cenomaniense superior y del Turoniense inferior en el á - Barroso Barcenilla, Fernando (Coloquios de Paleontología, 2004)
A detailed taxonomic analysis has been carried out including the Acanthoceratidae family ammonoids collected in the materials of the upper Cenomanian and lower Turonian appearing in the location of Puentedey, as weIl as in other sections belonging to neighbouring towns. All of them are located in northem Spain. Nineteen cephalopod genera and twenty-eight species have been identified, among which eight genera and fifteen species are included in the family Acanthoceratidae. Some of them are found in Spain for the first time, such as Euomphaloceras euomphalum and Fagesia catinus species. This research has made it possible to develop a biostratigraphic section which represents the observed cephalopod succession in the materials from the upper Cenomanian to the lower Turonian of Puentedey Formation series type, where eight ammonite biohorizons have been identified. This has enabled us to establish its zonal division. In the upper Cenomanian, three ammonite bioestratigraphic zones have been identified: Calycoceras (Calycoceras) naviculare, Metoicoceras geslinianum and Spathites (Jeanrogericeras) subconciliatus. The first one had not previously been used in the Basque-Cantabrian Basin and in it, the ammonite biohorizons Calycoceras (Calycoceras) naviculare and Neolobites vibrayeanus have been differentiated, whereas in the second one, two biohorizons have been characterized: Metoicoceras muelleri and Metoicoceras geslinianum. In the Lower Turonian the Choffaticeras quaasi and Mammites nodosoides zones have been identified, the first one including the Choffaticeras quaasi and Spathites (Ingridella) malladae biohorizons.